Evaluation of comprehensive benefits and the degree of coupling coordination for soil health products: a case study in Weifang City, China - Yuhu Cui; Jie Zhang; Xueshi Xie; Li Zhou; Wentao Wu; Lin Yang (Scientific Reports)
Abstract Evaluating the economic, social, and environmental benefits and coupling coordination of soil health products (SHPs) is required for rational soil science management and sustainable agricultural development. Therefore, this paper developed a comprehensive evaluation index system for Weifang City, Shandong Province, China, with the natural breakpoint method and a coupling coordination model to estimate the comprehensive benefits and coupling coordination of SHPs from 2018 to 2021. The comprehensive benefit scores exhibited a generally upward trend over time and regional spatial heterogeneity. However, the economic benefit scores were higher and more closely related to the planting goals of farmers, while the social benefit scores exhibited less fluctuation and lower regional heterogeneity, and the environmental benefit scores were low. In terms of the degree of coupling coordination, the economic, social, and environmental benefits of SHPs were found to be barely coordinated and on the verge of disorder, with distinct spatial distribution characteristics. The disorder of each system was affected by multiple compound factors and significant uncertainty. The results of the present study thus provide a theoretical foundation for decision-making by government and agricultural organizations regarding the use of SHPs.